Listeriolysin O Secreted by Listeria monocytogenes into the Host Cell Cytosol Is Degraded by the N-End Rule Pathway - Schnupf, Pamela (American Society for Microbiology (ASM), 2007)
The intracellular pathogen Listeria monocytogenes escapes from a phagosomal compartment into the cytosol by secreting the pore-forming cytolysin listeriolysin O (LLO). During the proliferation of L. monocytogenes bacteria in the mammalian cell cytosol, the secreted LLO is targeted for degradation by the ubiquitin system. We report here that LLO is a substrate of the ubiquitin-dependent N-end rule pathway, which recognizes LLO through its N-terminal Lys residue. Specifically, we demonstrated by reverse-genetic and pharmacological methods that LLO was targeted for degradation by the N-end rule pathway in reticulocyte extracts and mouse NIH 3T3 cells and after its secretion by intracellular bacteria into the mouse cell cytosol. Replacing the N-terminal Lys of LLO with a stabilizing residue such as Val increased the in vivo half-life of LLO but did not strongly affect the intracellular growth or virulence of L. monocytogenes. Nevertheless, this replacement decreased the virulence of L. monocytogenes by nearly twofold, suggesting that a destabilizing N-terminal residue of LLO may stem from positive selection during the evolution of this and related bacteria. A double mutant strain of L. monocytogenes in which upregulated secretion of LLO was combined with a stabilizing N-terminal residue was severely toxic to infected mammalian cells, resulting in reduced intracellular growth of bacteria and an ∼100-fold-lower level of virulence. In summary, we showed that LLO is degraded by the N-end rule pathway and that the degradation of LLO can reduce the toxicity of L. monocytogenes during infection, a property of LLO that may have been selected for its positive effects on fitness during the evolution of L. monocytogenes.